Diminishing differences in treatment between patients with colorectal cancer with and without diabetes: a population‐based study. Issue 10 (28th June 2013) - Zanders, M. M. J.; van, L. N.; Haak, H. R.; Rutten, H. J. T.; Pruijt, J. F. M.; Poortmans, P. M. P.; Lemmens, V. E. P. P.; van de, L. V.
Abstract Aims An increasing number of oncologists will be confronted with individuals having diabetes and cancer. We assessed changes in patient‐, tumour‐ and treatment‐related variables in patients with colorectal cancer with and without diabetes. Methods All 17 170 cases of primary colorectal cancer between 1995 and 2010 in the South‐Eastern Netherlands were included. The Cochrane–Armitage test and logistic regression analysis were used to analyse trends. Results In total, 11 893 patients were diagnosed with colon cancer and 5277 with rectal cancer, of whom 1711 (14%) and 609 (12%), respectively, had diabetes at the time of cancer diagnosis. Patients with colorectal cancer with diabetes compared with those without were approximately 5 years older and more often diagnosed with proximal colon tumours (60 vs. 54%; P < 0.0001). Chemotherapy administration significantly increased in patients with stage III colon cancer with and without diabetes (from 17% in 1995–1998 to 50% in 2007–2010, 38% to 63%, respectively; P < 0.0001). However, in the most recent period, and after adjusting for the co‐variables age, gender, year of diagnosis and specific co‐morbidities, patients with stage III colon cancer with diabetes received adjuvant chemotherapy less frequently than those without [odds ratio 0.7 (95% CI 0.5–0.9); P = 0.002]. The proportion of patients with stage II/III rectal cancer with and without diabetes who underwent radiotherapy has been similar in recent years (91 vs. 87%). Conclusions Although the administration of chemotherapy and radiotherapy increased between 1995 and 2010 in patients with colorectal cancer with and without diabetes, patients with colorectal cancer with diabetes continue to receive chemotherapy less frequently than those without diabetes.